PENDEKATAN TEOLOGIS DALAM KAJIAN ISLAM - Luk Luk Nur Mufidah (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2017)
As a science of divinity, theology has a significant role in efforts to form a mindset that will have implications for the religious person's behavior. To establish a mindset, it is necessary theological approaches that serves as a way to give birth to a new theological idea, whether it is traditional thinking, liberal, or modern. As a science of divinity, theology has a significant role in efforts to form a mindset that will have implications for the religious person's behavior. To establish a mindset, it is necessary theological approaches that serves as a way to give birth to a new theological idea, whether it is traditional thinking, liberal, or modern.As a science of divinity, theology has a significant role in efforts to form a pattern thought that would have implications for the religious person's behavior. To establish a mindset, it is necessary theological approaches that serves as a way to give birth to a new theological idea, whether it is traditional thinking, liberal, or modern. Of the various theological approaches exist, normatif theological approach is a theological approach in an effort to understand religion literally. This normatif approach can be interpreted as an attempt to understand religion using the framework of divinity revealed from a belief that empirical manifestation of a religion regarded as the most correct than others. Kata Kunci : Theology and Islamic Studies